Assessing the ecological consequences of biodegradable plastics: Acute, chronic and multigenerational impacts of poly-3-hydroxybutyrate microplastics on freshwater invertebrate Daphnia magna - Procházková, Petra; Kalčíková, Gabriela; Maršálková, Eliška; Brtnický, Martin; Zlámalová Gargošová, Helena; Kučerík, Jiří (CELL PRESS, 2024)
Microplastics, pervasive contaminants in freshwater ecosystems, have raised ecological concerns. Efforts are underway to substitute conventional plastics with biodegradable alternatives that should be more easily decomposed in the environment. However, the biodegradation of these alternatives depends on specific conditions such as temperature, humidity, pH, and microorganisms, which are not always met. Consequently, these biodegradable alternatives can also fragment and generate microplastics, which can be ingested and affect biota. In this study, we investigated the acute, chronic, and multigenerational effects of two fractions (particles <63 mu m and particles <125 mu m) of biodegradable poly-3-hydroxybutyrate (P3HB) at varying concentrations on the inhibition, mortality, reproduction activity, and growth of the freshwater invertebrate Daphnia magna. No acute effects were observed for either size fraction. However, during chronic and multigenerational experiments, an increase in the concentration of P3HB microplastics corresponded with increased mortality, reduced reproductive activity, and slower growth among the mother organisms. Given the important role of D. magna in the food chain, these findings suggest that biodegradable microplastics may indeed negatively affect freshwater ecosystems.

Microplastics, pervasive contaminants in freshwater ecosystems, have raised ecological concerns. Efforts are underway to substitute conventional plastics with biodegradable alternatives that should be more easily decomposed in the environment. However, the biodegradation of these alternatives depends on specific conditions such as temperature, humidity, pH, and microorganisms, which are not always met. Consequently, these biodegradable alternatives can also fragment and generate microplastics, which can be ingested and affect biota. In this study, we investigated the acute, chronic, and multigenerational effects of two fractions (particles <63 mu m and particles <125 mu m) of biodegradable poly-3-hydroxybutyrate (P3HB) at varying concentrations on the inhibition, mortality, reproduction activity, and growth of the freshwater invertebrate Daphnia magna. No acute effects were observed for either size fraction. However, during chronic and multigenerational experiments, an increase in the concentration of P3HB microplastics corresponded with increased mortality, reduced reproductive activity, and slower growth among the mother organisms. Given the important role of D. magna in the food chain, these findings suggest that biodegradable microplastics may indeed negatively affect freshwater ecosystems.
Assessing the ecological consequences of biodegradable plastics: Acute, chronic and multigenerational impacts of poly-3-hydroxybutyrate microplastics on freshwater invertebrate Daphnia magna
Keywords: P3HB; Biodegradable microplastics; Biofilm; D. magna; Reproduction; Growth; P3HB; Biodegradable microplastics; Biofilm; D. magna; Reproduction; Growth